Reply: Assessing the quality of evidence supporting patent foramen ovale closure over medical therapy after cryptogenic stroke - Ahmad,Y; Howard,J; Arnold,A; Shun-Shin,MJ; Cook,C; Francis,D; Sen,S (European Heart Journal, 2018)
This commentary refers to ‘Assessing the quality of evidence supporting patent foramen ovale closure over medical therapy after cryptogenic stroke’, by W.F. McIntyre et al., doi:10.1093/eurheartj/ehy496.